Single beam bathymetry processed data (Humminbird Helix 10 echosounder entire dataset), Israeli coastal estuaries Lachish, Sorek, Yarkon, Alexander, Taninim and Kishon - Yair Suari; Dror Suari; Yonatan Suari; Tal Sade; Hadar Sedaka; Tom Topaz (PANGAEA, 2023)
We present the data from a bathymetric mapping project in the Israeli coastal estuaries (Lachish, Sorek, Yarkon, Alexander, Taninim and Kishon). The data was collected using a combination of fish finder and GPS operated on a Kayak. The data preperation consisted of: a) manual removal of outliers which were mostly caused by instrument echo in water depths below the instrument 0.5 minimum. b) correction of the mesured water level to the sea level. c) interpolated into regular grid using a terrain following interpolation algorithm. For each of the streams we present the raw measurements, and the interpolated data both as text (csv) file and as GeoTiff file.